Modes, challenges and outcomes of nanotechnology transfer: A comparative analysis of university and company researchers - Christopher Palmberg (The Research Institute of the Finnish Economy (ETLA), 2007)
Nanotechnology has been proposed as the next general purpose technology and^engine for growth for the 21th century. Increasing public R&D investments are foremost reflected in the growth of scientific publications, while nanotechnology still is in an uncertain phase of development with various directions of commercialization pending. This paper focuses on the challenge, modes and outcomes of nanotechnology as an emerging science-based field in Finland. The paper contributes by interrogating how challenges and modes of nanotechnology transfer differ across universities and companies and determine outcomes broadly defined. It uses an extensive survey data covering university and company researchers in the Finnish nanotechnology community. The results show significant differences in the perceptions of researchers across these organisations, and highlight specific challenges and modes as determinants of outcomes. The specificities of nanotechnology are also assessed in this context.
Keywords: O31; O32; O38; 330; nanotechnology; technology transfer; Finland; survey data; Forschung; Nanotechnologie; Technologietransfer; Finnland